Thyrotoxicosis leading to adrenal crises reveals primary bilateral adrenal lymphoma. (16th May 2017) - Roque, Catarina; Fonseca, Ricardo; Bello, Carlos Tavares; Vasconcelos, Carlos; Galzerano, António; Ramos, Sância
Summary: Primary adrenal lymphoma is a rare malignancy. It frequently presents bilaterally and with symptoms of adrenal insufficiency. Amiodarone may induce secondary organ dysfunction, and thyrotoxicosis develops in 15% of cases. The symptomatology of both conditions is nonspecific, especially in the elderly, and a high suspicion index is necessary for appropriate diagnosis. A 78-year-old female presented to the emergency department with confusion, nausea and vomiting. She had recently been to the emergency department with urinary tract infection, vomiting and acute hypochloremic hyponatremia. Upon re-evaluation, the leukocyturia persisted and because of TSH 0.01 µU/mL and free-T4 68 (10–18) pmol/L, she was admitted to the Endocrinology ward. Further evaluation supported amiodarone-induced thyroiditis type 2. Sepsis ensued, in the setting of nosocomial pneumonia. Hemodynamic instability, hyponatremia, hypoglycemia and vomiting raised the suspicion of adrenocortical insufficiency. Fluid resuscitation and hydrocortisone led to clinical improvement, and adrenal insufficiency was admitted. The thoracoabdominal tomography suggested an endobronchic primary lesion with hepatic and adrenal secondary deposits (6.6 and 7 cm), but this was confirmed neither on pleural effusion nor on bronchofibroscopic fluid analyses. The adrenals were not accessible for biopsy. Despite high-dose hydrocortisone maintenance, the patient died before definite diagnosis. The autopsy confirmed primary non-Hodgkin lymphoma. Learning points: Primary adrenal lymphoma is a rare cause of adrenal insufficiency, but progression can be fast and fatal. Hyperpigmentation is frequently absent. The presenting symptoms are nonspecific and might mimic infection. Disproportion of the general state with signs of specific organ symptomatology is a diagnostic clue. Infection may precipitate adrenal crisis and worsen thyroid function with further adrenal insufficiency exacerbation. In the context of thyrotoxicosis, there may be little clinical response to a therapeutic trial with standard dose glucocorticoids. High-dose glucocorticoid substitution may be required to achieve clinical stability in thyrotoxic patients.